Nation building: Malaysia’s experience and lessons from the Sirah of al-Rasul s.a.w. - Zakariya, Hafiz (2018)
Malaysia is a federal constitutional monarchy located in Southeast Asia. Approximately 60% of its population professes Islam. It is a multi-ethnic and plural society. Malaysia has achieved independence for sixty years. After liberating itself from the grip of British colonialism, Malaysia faced a daunting task of developing its economy, designing education system suitable for its people, managing a fragile social relations among its diverse citizenry and charting its identity at the international arena. After six decades of historic independence, Malaysia’s process of nation building continues ensuring long term political stability. In navigating through this process, the Prophetic guidance on societal building is very crucial in providing useful ‘ibar (lessons) for policy makers and statesmen in Malaysia. Particularly important are the role of the Charter of Madinah (Sahifah Madinah) and the management of various ethnic/religious groups within Madinah .